Clinical pattern of superficial mycosis in rural type 2 diabetes mellitus patients - Gupta, Nikhil; Shukla, Vaibhav; Shukla, Priyanka (International Journal of Research in Medical Sciences, 2018)
Background: Diabetic foot infections are a major cause of amputations and mortality. There is heterogeneity in type of superficial fungal infections because of change in climatic conditions and lifestyles across world. There is paucity of reports on etiology of superficial fungal infections in rural type 2 diabetes mellitus patients in India, so the present study was undertaken to find out the clinical pattern of superficial fungal infections in rural type 2 diabetes mellitus patients. Methods: Rural type 2 diabetes mellitus patients clinically diagnosed to have superficial fungal infection were enrolled and were subjected to direct microscopy in KOH stain and fungal culture. Results: 100 type 2 diabetes mellitus patients were enrolled (58 males and 42 females). 45 were either KOH or culture positive. 73.1% were dermatophytes and rest nondermatophytes. Trichophyton rubrum was the commonest (48.8%) dermatophyte. Conclusions: Trichophyton rubrum was the commonest dermatophyte causing superficial infection. Besides dermatophytes non-dermatophytic fungi are also emerging as important cause of superfiicial mycosis.